Carbon electrode sensitivity enhancement for lead detection using polypyrrole, ionic liquid, and nafion composite - Zanu Saputra; Robeth Viktoria Manurung; Aminuddin Debataraja; Muhammad Iqbal Nugraha; Tien-Fu Lu (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2022)
This paper concerns enhancing a lead detection sensor using a combination of polypyrrole (PPy), Nafion (N), and ionic liquid (IL) with thick-film or screen-printing technology on sensitive material-based carbon electrodes. Electrode characterization using a scanning electron microscope (SEM) was conducted to see the morphology of sensitive materials, showing that the spherical particles were distributed evenly on the electrode surface. Analysis using energy dispersive spectroscopy (EDS) shows that the element's atomic composition is 84.92 %, 8.81 %, 6.26 %, and 0.01 % for carbon, nitrogen, oxygen, and bismuth, respectively. Potentiostat measurement with the ambient temperature of 25 °C on a standard lead solution with concentration ranging from 0.05 to 0.5 mg/l yields an average output voltage ranging from 2.16 to 2.27 V. It can be concluded that the sensor is able to detect lead with a sensitivity of 0.21 V in each addition of solution concentration (mg/l) and give an 84 % concentration contribution to the voltage.